Recent female incarceration in Brazil: a discussion from Rio de Janeiro, Manaus and Fortaleza - Ribeiro Gomes, Simone (Revista de Ciências Sociais, 2020)
This work aims to contribute to the understanding on the increase of the incarceration of women through reflecting on their involvement based on the Drug Law´s (Lei nº 11.343/2006). Starting on a fieldwork in feminine and masculine prisons, in three cities: Rio de Janeiro, Manaus and Fortaleza, as well as semistructered interviews with actors from the penitentiary system, the text revolves around the role of women doing sentence, on the reconfiguration, drifting in the maintenance and reorganization of prison gangs, inside and outside prisons. A literature review was done, in which studies of gender, articulated to the prison literature were listed, as well as classical texts from the sociology of violence.